Strive or thrive: Trends in Phytophthora capsici gene expression in partially resistant pepper - Maillot, Gaëtan; Szadkowski, Emmanuel; Massire, Anne; Brunaud, Véronique; Rigaill, Guillem; Caromel, Bernard; Chadœuf, Joël; Bachellez, Alexandre; Touhami, Nasradin; Hein, Ingo; Lamour, Kurt; Balzergue, Sandrine; et al. (Frontiers in Plant Science, 2022)
Partial resistance in plants generally exerts a low selective pressure on pathogens, and thus ensuring their durability in agrosystems. However, little is known about the effect of partial resistance on the molecular mechanisms of pathogenicity, a knowledge that could advance plant breeding for sustainable plant health. Here we investigate the gene expression of Phytophthora capsici during infection of pepper (Capsicum annuum L.), where only partial genetic resistance is reported, using Illumina RNA-seq. Comparison of transcriptomes of P. capsici infecting susceptible and partially resistant peppers identified a small number of genes that redirected its own resources into lipid biosynthesis to subsist on partially resistant plants. The adapted and non-adapted isolates of P. capsici differed in expression of genes involved in nucleic acid synthesis and transporters. Transient ectopic expression of the RxLR effector genes CUST_2407 and CUST_16519 in pepper lines differing in resistance levels revealed specific host-isolate interactions that either triggered local necrotic lesions (hypersensitive response) or elicited leave abscission (extreme resistance), preventing the spread of the pathogen to healthy tissue. Although these effectors did not unequivocally explain the quantitative host resistance, our findings highlight the importance of plant genes limiting nutrient resources to select pepper cultivars with sustainable resistance to P. capsici.